Surgical treatment of lung sequestration - Cvijanović Vlado; Stanić Vojkan; Ristanović Aleksandar; Gulić Bojan; Stamenović Davor; Marić Nebojša; Kovačević Snežana; Zolatarevski Lidija (Vojnosanitetski Pregled)
Background/Aim. Pulmonary sequestration is a congenital malformation which consists of a functional part of the lung, separated of the normal airway, and vascularisated with anomal systemic artery instead of pulmonary artery. There are two kinds of sequestration. Intralobar is surrounded with normal lung and its pleura, and extralobar which has extrapulmonary position and pleura of its own. This anomaly is very rare and appears in 1.1−1.8% of all congenital lung malformations. The illness is revealed either in early childhood with other life-threatening anomalies or in adulthood and middle age when secondary infection arises. The aim of this paper was to show our own experience in surgical treatment of pulmonary sequestration and to emphasize sequestration as a real differential-diagnostic possibility with patients with recidive bronchopneumonias. Methods. We retrospectively analyzed medical records for the period from 1967−2007 and found 15 patients with pulmonary sequestration at the average age of 30 years. We pointed out the well known problems with identification of this anomaly, preoperative diagnostic procedures and surgical possibilities of treatment. Results. There were 13 patients with intralobar and two patients with extralobar sequestration. By the use of preoperative angiography, seven patients were found to have intralobar pulmonary sequestration. All intralobar sequestrations were clinically manifested, the most often with recidive bronchopneumonia. Six patients had no preoperative diagnosis of lung sequestration. The most common locality of intralobar sequestration was the left lower lobe (eight patients). We performed nine lobectomies, three sequestrectomies, two segmentectomies and one pneumonectomy. Both extralobar sequestrations were diagnosed intraoperatively. Conclusion. Pulmonary sequestration is a rare malformation. Diagnosis is established by angiography. Treatment is exclusively surgical. In the last three years we have had one patient per year. This experience obliges to consider pulmonary sequestration as a real differential- diagnostic possibility in patients with localized repeated bronchopneumonias.